Pengaruh Gaya Kepemimpinan Dan Komitmen Pegawai Terhadap Kinerja Pns Pada Kantor Kelurahan Di Kecamatan Cipedes Kota Tasikmalaya - Risda Tristianti; Arga Sutrisna; Titin Patimah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of leadership style and employee commitment on the performance of civil servants at the village office in Cipedes sub-district, Tasikmalaya city. This study uses a descriptive quantitative method. The types of data used are primary data and secondary data, with a sample of 41 respondents from civil servants at the Village Office in Cipedes District, Tasikmalaya City, and using the saturated sample method. The data analysis tool used in this study was SPSS Version 25. Data collection techniques used observation, interviews, questionnaires, and literature studies. Leadership Style and Employee Commitment simultaneously have a significant effect on Employee Performance in Civil Servants at the Village Office in Cipedes District, Tasikmalaya City. Leadership Style partially has a significant effect on Civil Servant Performance. Employee Commitment partially has a significant effect on Civil Servant Performance.